Conjoint analysis of Singapore private residential property buyer's behaviours. - Loo, Chuen Yew. (2009)
The objective of this study is to investigate the preferences of Singapore private residential property buyers for difference types of condominiums. The study values the relative importance of property attributes such as location, price, tenure, size and finish, as seen by potential buyers. Survey data is analysed using a conjoint measurement approach, through the SPSS Categories software package. The utilities and importance results obtained for each factor indicates that freehold tenure is the most sought after attribute. But after considering all the trade-offs, price is the key factor influencing Singaporeans' condominium buying decision. Further examination of the results suggests that Singaporeans place a high emphasis on the investment value of a property even when they consider buying the property for self-occupancy.